2021
DOI: 10.2147/clep.s312132
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Future Caries Occurrence Among Preschoolers in Northern Guangdong: A Longitudinal Study

Abstract: This study aimed to investigate the new development of caries among preschoolers in northern Guangdong and to assess caries-related factors to distinguish groups with different caries risk levels. Methods: Baseline data were recorded for participants from September to November 2019, and participants were reexamined from September to November 2020. A longitudinal observation of 11,973 preschoolers was conducted. The simplified debris index (DI-S) and decayed-missing-filled tooth (dmft) index values were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…Nineteen studies had age as a predictor. Of 19, nine studies reported age as significantly associated with future caries risk (ORs: 1.10–5.00; HRs: 1.70, 1.77, 1.83; RRs: 1.07, 1.12) 19–27 . Only four of 25 studies reported a significant association for sex as a predictor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nineteen studies had age as a predictor. Of 19, nine studies reported age as significantly associated with future caries risk (ORs: 1.10–5.00; HRs: 1.70, 1.77, 1.83; RRs: 1.07, 1.12) 19–27 . Only four of 25 studies reported a significant association for sex as a predictor.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, as their jaws develop and grow, there is a higher likelihood of food impaction between primary teeth, leading to a greater risk of interproximal decay. 25 Certain clinical factors have been linked to ECC. The presence of dental plaque is a reliable and widely recognized sign that can help in the identification of the initial phases of ECC and also in assessing the extent or severity of the condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan jabaran tersebut dapat diakatakan bahwa kemapuan motorik kasar anak masih belum optimal. Dengan demikian, guru harus menciptakan kesempatan belajar yang tepat agar anak-anak mengalami berbagai latihan motorik di tempat yang sesuai, dilengkapi dengan materi khusus, dan mereka harus siap untuk melakukan kegiatan pendidikan khusus yang mempertimbangkan karakteristik dan kebutuhan individu anak (Yan et al, 2021).…”
Section: Pendahuluanunclassified
“…In the past 10 years, with the rapid economic development of Guangdong Province, China, the government has invested a large amount of manpower and material resources in the prevention and treatment of children's caries. However, the prevalence of children's caries is still increasing ( 1 ). The caries-free rate of primary teeth of children aged 5 years (21.6%) was far lower than the World Health Organization's (WHO) target of a 50% caries-free rate, and the filled rate of dental caries was only 1.3% ( 2 ).…”
Section: Introductionmentioning
confidence: 99%